The symbol in Ahmed Matar's poetry (Journal of the College of Basic Education, 2022)
The symbol is one of the means used in the modern poem, which gives it an active role in poetrygiving the text a suggestive energy; So the Iraqi poet Ahmed Matar resorted to enriching his text with it, even a special oneimportant in the poem Al-Matariyya being a convenient means of satirizing reality; The form of a special poetic visionBy him, he reshaped and formulated it through his images; The language of the symbol has one of the loving expression methodsAnd expressive of his creative poetic experience of the poet.Ahmed Matar dealt with two types of symbols: they are natural symbols; and iconshumanity; Through them, he devised means that distinguished him from other poets of his generation until I became knownThose symbols done as rooms made .